ADAPTABILITY AND PRODUCTION PRACTICES OF MILLET (KABOG) GROWN UNDER CSCST- BARILI CAMPUS CONDITION - Borbon, SM; Pascual, ML; Pasaje, GM (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
Studies on millet production practices were conducted at CSCST-Barili Campus research experimental site to determine: 1) the effects of the different methods of seeding, 2) individual effects of planting distance and plant density as well as their interaction effects, and 3) individual effects of the time and the rate of fertilizer application as well as the interaction effects of the two on the growth and yield performance of millet. Planting seeds by dropping into holes (T1) resulted to a significantly higher plant height, aboveground and underground biomass, number of tillers and panicles per hill, panicle length, weight of panicle and weight of grains per panicle as compared when seeds were drilled along the furrows (T2) and by broadcasting (T3). Plants planted at closer space (Pd1 and Pd2) had taller plant height than plants planted at wider space (Pd3). At 25cm x 25cm planting distance, plants had higher above ground biomass, more number of tillers produced as compared to the other planting distances (Pd1 and Pd3). Significant differences were observed in the result of the under-ground biomass, weight of panicle per hill, weight of grains per panicle and grain yield. Almost similar results were obtained in the number of tillers produce per hill. In terms of plant density, more number of tillers and panicles per hill in D3 (3 plant/hill) than D1 (1 plant/hill) and D2 (2 plants/hill) were observed. But the length and weight of panicle as well as the weight of grains per panicle were lower in D3. Significant differences were observed between plant distance and plant density in terms of number of days from planting to panicle initiation, plant height, above and underground biomass, number of tillers, weight of panicle per hill and grain yield per plot. While, not significant difference were observed in panicle length and weight of grains per panicle. Plants applied with fertilizer at 30 DAP had higher results as compared to plants applied with fertilizer at 45 DAP. Significant difference was observed in the rate of fertilizer application in all the growth and yield parameters gathered. Significant difference was observed in the rate of fertilizer application in all the growth and yield parameters gathered. Plant height was significantly affected by the rate of fertilizer applied while the underground biomass and weight of grain per panicle were significantly affected by the time of fertilizer application. Significant differences were observed between the interaction effect of rate and time of fertilizer application to the growth and yield of millet.